Biological Parameters and Stock Status of Crimson Snapper (Lutjanus erythropterus) in Indonesia FMA 712 based at Brondong Fishing Port - Listyanto Putri, Adjeng Peni; Taurusman, Am Azbas; Wahju, Ronny Irawan (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research This research highlight presents a focused summary of the key findings from our study in the field of fisheries science, specifically addressing the biological parameters and stock status of economically important fish species. There is highlighted research presented in this study, namely: Crimson snapper in PPN Brondong is captured using four types of fishing gear: cantrang, jaring tarik berkantong, handline, and bottom longline. The growth pattern of the crimson snapper is negative allometric. The Gonad Maturity Level (GML) of the catch was predominantly composed of crimson snapper at GML I and GML II. The asymptotic length (L∞) of crimson snapper was 47.68 cm, with K = 0.4 per year, total mortality (Z) = 2.44 per year, natural mortality (M) = 0.98 per year, capture mortality (F) of 1.55 per year, and exploitation rate (E) = 0.60 The estimated value of the crimson snapper SPR was 22% suggesting that the crimson snapper stock is ‘fully exploited’. Abstract The utilization status of crimson snapper stock in the Northern Java Sea (FMA 712) has reached optimum, tending to be over-exploited. This study aims to evaluate the stock status of crimson snapper (Lutjanus erythropterus) in FMA 712, especially in the northern waters of East Java. This research utilized catch data from the Brondong fishing port. The stratified random sampling method was utilized to collect samples at the research site. The findings indicate that the growth pattern of L. erythropterus exhibits a tendency towards negative allometry, with fishing mortality (F = 1.55) exceeding natural mortality (M = 0.89). The exploitation rate has reached a status of ‘fully exploited’ (E = 0.6). The Gonad Maturity Level (GML) of the catch is predominantly composed of GML I and GML II, suggesting that the majority of the captured fish have not yet spawned. It relates to the predominance of cantrang and jaring tarik berkantong, which capture fish of juvenile size. Thus, the Spawning Potential Ratio (SPR) parameter indicates it is ‘fully exploited’ (SPR = 0.22), i.e., the utilization rate has exceeded the limit of natural capacity for recruitment. This SPR value confirms: the utilization rate parameter (E), the fact that catch sizes tend to get smaller, and the results of previous studies in FMA 712. It is imperative to regulate the fishing efforts targeting the crimson snapper, as well as the deployment of cantrang and jaring tarik berkantong, which pose potential threats to the sustainability of this fishery.